Out of control online? A combined examination of peer-offending and perceived formal and informal social control in relation to system-trespassing - Berenblum, Tamar (Journal of crime and justice, 2019)
Compared to the offline world, the online environment is more anonymous and therefore less easily controlled. Criminological theories generally show that people are more likely to commit crime when they experience or perceive less formal or informal social control. Consequently, one might assume that people are more likely to commit crime online than offline. As formal social control is lacking, informal social control and peer-offending may be important predictors of online offending. In this paper, we examine to what extent differences in perceived formal and informal online control are related to the likelihood that a person will commit a system-trespassing offense (i.e. malicious hacking). Additionally, we examine peer system-trespassing, and how this may interact with perceptions of formal and informal social control. In the logistic regression analyses we employ eight different measures for perceptions of formal and informal social control, in addition to peer-offending, and control variables. Both direct effects and interaction effects are examined. Our results show that peer-offending is an important predictor of system-trespassing and interaction effects show that perceived formal and informal online social control are related to this type of offending but only for specific groups. Implications will be discussed.